2017
DOI: 10.3892/mmr.2017.8364
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits HaCaT cell viability via the miR-21/PTEN/Akt signaling pathway

Abstract: Substantial preclinical evidence has indicated out a direct anti‑proliferation effect of metformin on various solid tumors; however, further and more detailed exploration into its molecular mechanism remains to be performed. The present study aimed to investigate the effect of metformin on cell viability and its underlying mechanism, in the cultured human skin keratinocyte cell line, HaCaT. In addition, it aimed to clarify the role of the microRNA-21(miR-21)/phosphatase and tensin homolog (PTEN)/AKT serine/thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…PTEN plays complex roles in multiple cellular processes including proliferation, survival, apoptosis, cell cycle regulation, adhesion, and migration [21,44]. In our study, PTEN expression was reduced upon MTFN treatment, in line with previous studies [45,46], but this reduction was compensated following MTFN/CURC co-treatment. Cell death induction by co-treatment suggests that the co-presence of MTFN and CURC may strengthen the anti-tumor activities of PTEN via engaging several pathways and factors including miR-21 and Akt/PI3K [47].…”
Section: Discussionsupporting
confidence: 91%
“…PTEN plays complex roles in multiple cellular processes including proliferation, survival, apoptosis, cell cycle regulation, adhesion, and migration [21,44]. In our study, PTEN expression was reduced upon MTFN treatment, in line with previous studies [45,46], but this reduction was compensated following MTFN/CURC co-treatment. Cell death induction by co-treatment suggests that the co-presence of MTFN and CURC may strengthen the anti-tumor activities of PTEN via engaging several pathways and factors including miR-21 and Akt/PI3K [47].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it was also reported that the expression of PTEN was significantly higher in skeletal muscle cells with glucose-induced insulin resistance than that in normal skeletal muscle cells, and metformin significantly reduced insulin resistance by decreasing the expression levels of PTEN in these cells (54). In human keratinocyte cell lines, metformin was found to inhibit cell growth in a dose-dependent manner by inhibiting the miR-21/PTEN/AKT pathway (55). The present study showed that the increased expression levels of PTEN in PA-treated EPcs were reversed by treatment with metformin or by the overexpression of miR-130a induced by miR-130a mimics.…”
Section: Discussionmentioning
confidence: 96%
“…After transfection of miR-21 mimics, metformin could reduce the expression levels of miR-21 and change the expression of downstream signaling proteins. The inhibitory effect of metformin on miR-21 has been veri ed in various tumors and endothelium [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%